Scale‐up manufacturing of gelatin‐based microcarriers for cell therapy. Issue 7 (1st May 2020) - Dosta, Pere; Ferber, Shiran; Zhang, Yi; Wang, Kui; Ros, Albert; Uth, Nicholas; Levinson, Yonatan; Abraham, Eytan; Artzi, Natalie
Abstract: Microcarriers, including crosslinked porous gelatin beads (Cultispher G) are widely used as cell carriers for cell therapy applications. Microcarriers can support a range of adherent cell types in stirred tank bioreactor culture, which is scalable up to several thousands of liters. Cultispher G in particular is advantageous for cell therapy applications because it can be dissolved enzymatically, and thus cells can be harvested without the need to perform a large‐scale cell‐bead filtration step. This enzymatic dissolution, however, is challenged by the slow degradation of the carriers in the presence of enzymes as new extracellular matrix is being deposited by the proliferating cells. This extended dissolution timelimits the yield of cell recovery while compromising cellular viability. We report herein the development of crosslinked porous gelatin beads that afford rapid, stimuli‐triggered dissolution for facile cell removal using human mesenchymal stem cells (hMSC) as a model system. We successfully fabricated redox‐sensitive beads (RS beads) and studied their cell growth, dissolution time and cell yield, compared to regular gelatin‐based beads (Reg beads). We have shown that RS beads allow for much faster dissolution compared to Reg beads, supporting better hMSC detachment and recovery following 8 days of culture in spinner flasks, or in 3L bioreactors. These newly synthesized RS beads show promise as cellular microcarriers and can be used for scale‐up manufacturing of different cell types while providing on‐demand degradation for facile cell retrieval.